Designing Incentive Systems for Truthful Forecast Information Sharing Within a Firm - Scheele, Lisa M.; Thonemann, Ulrich W.; Slikker, Marco (Management Science, 2018)
We consider a firm where the sales division (Sales) is responsible for demand forecasting and the operations division (Operations) is responsible for ordering. Sales has better information about the demand than Operations and sends a nonbinding demand forecast to Operations. To incentivize truthful information sharing, we include a forecast error penalty in the incentive system of Sales. Besides monetary payoffs, we also add behavioral factors to the utility function of Sales. We model the setting as a signaling game and derive the Pareto-dominant separating equilibria of the game. In laboratory experiments, we observe human behavior that is in line with the predictions of the behavioral model but deviates substantially from expected-payoff-maximizing behavior. We use the behavioral model to design incentive systems for truthful information sharing and validate the approach in an experiment with out-of-sample treatments and out-of-sample subjects. We conduct additional experiments to provide further robustness to the results. The experimental data and e-companion are available at https://doi.org/10.1287/mnsc.2017.2805 . This paper was accepted by Martin Lariviere, operations management.